The hero and the perennial journey home in American film - Mackey-Kallis, Susan (University of Pennsylvania Press, 2001)
In contemporary America, myths find expression primarily in film. What's more, many of the highest-grossing American movies of the past several decades have been rooted in one of the most fundamental mythic narratives, the hero quest. Why is the hero quest so persistently renewed and retold? In what ways does this universal myth manifest itself in American cinema? And what is the significance of the popularity of these modern myths?The Hero and the Perennial Journey Home in American Film by Susan Mackey-Kallis is an exploration of the appeal of films that recreate and reinterpret this mythic structure. She closely analyzes such films as E.T., the Star Wars trilogy, It's a Wonderful Life, The Wizard of Oz, The Lion King, Field of Dreams, The Piano, Thelma and Louise, and 2001: A Space Odyssey. Elements of the quest mythology made popular by Joseph Campbell, Homer's Odyssey, the perennial philosophy of Aldous Huxley, and Jungian psychology all contribute to the compelling interpretive framework in which Mackey-Kallis crafts her study. She argues that the purpose of the hero quest is not limited to the discovery of some boon or Holy Grail, but also involves finding oneself and finding a home in the universe. The home that is sought is simultaneously the literal home from which the hero sets out and the terminus of the personal growth he or she undergoes during the journey back. Thus the quest, Mackey-Kallis asserts, is an outward journey into the world of action and events which eventually requires a journey inward if the hero is to grow, and ultimately necessitates a journey homeward if the hero is to understand the grail and share it with the culture at large. Finally, she examines the value of mythic criticism and addresses questions about myth currently being debated in the field of communication studies.